Hydrophilic injectable dermal filler composition and its preparation method and use
The combination of polymer microspheres and cross-linked sodium hyaluronate with mussel adhesion protein in dermal fillers addresses misalignment and aggregation issues, ensuring stable, precise, and biocompatible long-term collagen stimulation.
Patent Information
- Application Number
- JP2022166948
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-26
- Filing Date
- 2022-10-18
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2042-10-18
AI Technical Summary
Current injectable dermal fillers face issues such as poor affinity with human skin, misalignment during injection, sedimentation, and reduced effectiveness due to aggregation, leading to adverse reactions like nodules and inflammation.
A composition of polymer microspheres, specifically polylactic acid-polycaprolactone-polyethylene glycol copolymer, combined with cross-linked sodium hyaluronate and mussel adhesion protein, stabilized by polyethylene glycol succinimidyl glutarate, forming a biomimetic extracellular matrix structure for precise adhesion and sustained collagen stimulation.
The composition provides stable, precise filling with reduced adverse reactions, immediate filling effect, and long-term collagen stimulation, maintaining dispersion and biocompatibility, while minimizing displacement and inflammation.
Smart Images

Figure 0007604433000001 
Figure 0007604433000002
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of medicine, in particular to a hydrophilic injectable dermal filler composition and its preparation method and use. [Background technology]
[0002] In recent years, injectable fillers in aesthetic medicine have developed rapidly with the expansion of the aesthetic medicine industry, and as people's sense of beauty and the importance of safety and health have increased, safe and effective injectable products have been attracting widespread attention. However, filling products such as microspheres and sodium hyaluronate currently available on the market for injectable filling have poor affinity with human skin, are prone to misalignment of the injection site, and have poor dispersibility of microspheres, which makes it difficult to guarantee stable effects for a long period of time after injection due to factors such as susceptibility to sedimentation and aggregation.
[0003] Artificially chemically synthesized polymer microspheres have a lower risk of infection than animal-derived fillers, have relatively good safety, and have a long retention time, but lack good biocompatibility.Sodium hyaluronate is a filler with good biocompatibility and a relatively wide range of uses, but the problem of slippage during filling is often raised, and the effect of filling is greatly reduced due to the slippage of the injection position.That is, although sodium hyaluronate has good biocompatibility, it is not the best injection filler because of its poor adhesion effect with human cells.
[0004] Chinese Patent Application No. 201980018465.0 discloses polycaprolactone microsphere filling containing collagen peptides and its manufacturing method, but polycaprolactone is prone to clumping, which reduces the effect of the microspheres in stimulating collagen production and may cause adverse reactions such as nodules, making it an undesirable injectable filling material. In response to the above problems, there is a need to develop a new injectable dermal filler composition. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the problems in the past, the present invention aims to provide a hydrophilic injectable dermal filling composition that has good biocompatibility, is capable of reducing the incidence of adverse reactions such as subcutaneous nodules and inflammation after injection, has good immediate filling effect, and is not easily displaced, as well as a preparation method and use thereof. [Means for solving the problem]
[0006] To achieve the above objectives, the technical solution of the present invention is as follows: The present invention is a composition comprising polymer microspheres, polyethylene glycol succinimidyl glutarate (PEG-SG), and a dispersion, wherein the polymer microspheres are polylactic acid-polycaprolactone-polyethylene glycol copolymers, and the dispersion comprises cross-linked sodium hyaluronate and a protein, wherein the protein is a mussel adhesive protein or a fibroin protein. Effect of the Invention
[0007] The present invention provides a method for the preparation of a composition system by using a polymer microsphere having a specific amphiphilicity in combination with a dispersion liquid containing a specific component, which allows the protein, PEG-SG and cross-linked sodium hyaluronate to be mixed with each other, and the composition system can be rapidly converted from a liquid state into a specific solid-liquid interpenetrating gel biomimetic extracellular matrix structure, thereby enabling the polymer microsphere of the present invention to be stably present in the composition system in a specific dispersion form, and the composition thus obtained is less likely to slip, has a low swelling rate, has an immediate filling effect on the target and has good biocompatibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In order to better achieve the effects of wide-area cell adhesion and localization, local anti-oxidation, anti-inflammation, site filling and injection site repair, it is preferred that the protein is a mussel adhesive protein.
[0009] In the present invention, the mass ratio of the protein to the cross-linked sodium hyaluronate is 1:(15-25), preferably 1:20; And / or, the mass ratio of the cross-linked sodium hyaluronate to the polyethylene glycol succinimidyl glutarate is (80 to 120):1, preferably 100:1. In the present invention, in order to achieve a better immediate target loading effect and a sustained stimulating effect on proliferation, the ratio of the total mass of the polyethylene glycol succinimidyl glutarate and the dispersion liquid to the mass of the polymer microsphere is (6-9):(1-4), preferably 7.5:2.5. The preferred ratio of the above-mentioned materials of the present invention has better uniform dispersion and immediate loading effect of the microspheres.
[0010] In the present invention, in order to obtain a better filling effect with low swelling, the dispersion liquid further contains a phosphate buffer solution and glycerol, and has an osmotic pressure of 250-350mOsm / L; the concentration of the cross-linked sodium hyaluronate in the dispersion liquid is 15-30mg / ml, preferably 24mg / ml; And / or, in order to achieve a better balance between fluidity and moisture retention, the mass fraction of the glycerol in the dispersion is 0.48 to 2%, and preferably 1%. The phosphate buffer in the dispersion of the present invention allows the composition of the present invention to be isotonic with the human body, preferably having a pH of 7.3.
[0011] In the present invention, the intrinsic viscosity of the polymer microsphere is 0.15 to 1.5 dl / g (a 0.5% chloroform solution is prepared at 25°C with reference to the viscosity measurement method of Chinese Pharmacopoeia 20200663), and the proportion of PCL in the polymer is 40 to 70 wt%. In order to more suitably achieve both the stimulating effect on collagen proliferation and the hydrophilic effect, it is preferable that the intrinsic viscosity of the polymer microsphere is 1.2 dl / g, and the proportion of PCL in the polymer is 50 wt%. and / or the polyethylene glycol succinimidyl glutarate is 4-armed and has a molecular weight of 5,000 to 40,000, preferably 10,000; And / or, the molecular weight of the crosslinked sodium hyaluronate is 1,000,000 to 2,500,000, preferably 1,500,000. In the present invention, the crosslinking agent in the crosslinked sodium hyaluronate is divinyl sulfone, and the specific crosslinking method is to dissolve 1g of sodium hyaluronate in the sodium hydroxide solution with a mass fraction of 10%, add 5mg of divinyl sulfone and stir to obtain crosslinked sodium hyaluronate, and finally add 1mol / L of hydrochloric acid solution to adjust the pH value to 7.0-7.4. In the present invention, the molecular weight, viscosity and compounding ratio of the main raw materials can be adjusted according to the application site of the polymer microsphere and the demand for recovery effect to achieve different degradation times (the degradation period can be from 1 year to 5 years). The viscosity of the polymer microspheres of the present invention, the molecular weight of the protein and cross-linked sodium hyaluronate, and the blending ratio of each substance can achieve a balance between the dispersibility, injectability, degradability, and localization performance of the composition. The polymer microspheres of the present invention preferably have a particle size in the range of 35 to 45 μm.
[0012] The present invention also provides a method for preparing the above composition, comprising the step of producing polymeric microspheres by shear emulsification, membrane emulsification or spray drying. In order to achieve better target particle size distribution and yield of microspheres, the preparation method of polymer microspheres is preferably the membrane emulsification method. Specifically, the method for producing polymer microspheres includes a step of obtaining an oil phase by mixing an organic solvent with a polylactic acid-polycaprolactone-polyethylene glycol copolymer, and the organic solvent is one or more of dichloromethane, tetrahydrofuran, and chloroform, and dichloromethane or a mixed solvent of tetrahydrofuran and dichloromethane in a volume ratio of (1-2):(8-10) is preferred.
[0013] In the present invention, when the production is carried out by the shear emulsification method or the membrane emulsification method, a step of obtaining an aqueous phase by mixing an emulsifier with water is further included, and the emulsifier is one or more of polyvinyl alcohol, Span, Tween, and carboxymethyl cellulose, and polyvinyl alcohol or a mixed solvent of polyvinyl alcohol (viscosity 5 to 50 mPa s) and Tween 80 in a mass ratio of (9 to 10:1) is preferred; And / or, the volume ratio of the oil phase to the aqueous phase is 1:(4 to 10). In the present invention, the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer in the oil phase is 2 to 15%, and the mass fraction of the emulsifier in the aqueous phase is 0.1 to 3%.
[0014] In the present invention, when preparing polymer microspheres, the specific concentration of oil phase and the composition and concentration of water phase can ensure a better physical morphology of the microspheres obtained after emulsification, specifically, the microspheres obtained have good sphericity, narrow particle size distribution, smooth surface, and ideal yield. In a preferred embodiment, when the membrane emulsification method is used to produce the microspheres, the organic solvent is tetrahydrofuran and dichloromethane in a volume ratio of 1:9, the mass fraction of polylactic acid-polycaprolactone-polyethylene glycol copolymer in the oil phase is 8%, the mass fraction of the emulsifier in the aqueous phase is 1%, and the volume ratio of the oil phase to the aqueous phase is 1:6, in order to achieve a better target microsphere yield. When production is performed by the membrane emulsification method, the oil phase is permeated through a membrane at a pressure of 0.1 to 0.4 kPa, and then mixed with the aqueous phase while stirring at 4 to 8°C (the stirring speed is 200 to 500 r / min, and the pore size of the membrane is 10 to 20 μm). After completion of the permeation of the oil phase through the membrane, stirring (200 to 500 r / min) is continued to emulsify for 10 to 60 minutes, and then stirring (200 to 500 r / min) is continued at 15 to 25°C to volatilize the solvent in the oil phase. The produced microspheres are preferably washed multiple times until no solvent remains in the aqueous phase (washed with water 3 to 5 times), and then sieved to obtain microspheres having the target particle size. After the oil phase has been completely permeated through the membrane, the stirring speed used for emulsification (at 4 to 8°C) by continued stirring, and for volatilization of the oil phase solvent by continued stirring at 15 to 25°C, is the same as the stirring speed used for mixing the oil phase and the aqueous phase. When the oil phase is permeated through a membrane and mixed with the aqueous phase at 4 to 8°C with stirring, when stirring is continued to emulsify, and when stirring is continued at 15 to 25°C to volatilize the solvent in the oil phase, it is preferable that the speed is 250 r / min, the pressure for extruding the oil phase is 0.2 kPa, the pore size of the membrane is 20 μm, and the solvent in the oil phase is volatilized by stirring continuously at 15 to 25°C for 4 hours.
[0015] When producing by shear emulsification, the oil phase is dropped into the aqueous phase while stirring at 4 to 8° C. (the stirring speed is 800 to 1000 r / min for 20 to 40 minutes), and then the mixture is stirred at 400 to 500 r / min for 3 to 5 hours at 15 to 25° C. During mixing, it is preferable that the stirring speed is 1000 r / min for 30 minutes, and then the mixture is stirred at 500 r / min for 5 hours at 15 to 25° C.
[0016] When the oil phase is produced by spray drying, the oil phase is spray dried, and the inlet temperature during the spray drying process is 60-85° C., the outlet temperature is 25-50° C., the supply rate is 10-25 ml / min, and the high-pressure air flow rate is 400-600 L / hr. It is preferable that the inlet temperature is 85° C., the outlet temperature is 25° C., the supply rate is 25 ml / min, and the high-pressure air flow rate is 600 L / hr.
[0017] In the method for producing polymer microspheres of the present invention, the characteristics of the raw materials for producing microspheres can be effectively combined by using a combination of various conditions, and an ideal production effect can be achieved. In the present invention, the obtained polymer microspheres are first sieved, and then uniformly mixed with a dispersion liquid and PEG-SG in a specified ratio to obtain the above composition.
[0018] The present invention also provides the use of the composition, or a composition prepared by the method, in an injectable dermal filler product. The composition obtained by the present invention can be used for subcutaneous filling injections that are not intended for the diagnosis or treatment of diseases, and can provide a relatively long-lasting recovery effect by stimulating the generation of collagen in the deep layers of the skin itself. Specifically, it can be applied to the face and neck to achieve a cosmetic effect.
[0019] The present invention has at least the following beneficial effects: The composition of the present invention has good resolubility and high biocompatibility, can reduce inflammatory reactions after injection of the material, has antioxidant effects and injection site recovery effects, and the adhesion effect of the protein in the specific gel system of the present invention to cells can realize the accuracy and fixation of the injection position and eliminate the risk of filling material shifting. Furthermore, the composition of the present invention has a specific interpenetrating network structure that can maintain the suspending and dispersing effect of microspheres, and can provide an immediate filling effect. In addition, the polymer microspheres prepared by the method of the present invention have a narrow particle size distribution, high sphericity, and smooth surface, which can more effectively reduce the incidence of adverse reactions such as uneven decomposition, subcutaneous nodules, and red swelling after injection. EXAMPLES
[0020] Hereinafter, preferred embodiments of the present invention will be described in detail using examples. It should be understood that the following examples are for illustrative purposes only and are not intended to limit the scope of the present invention. Those skilled in the art can make various modifications and changes to the present invention without departing from the spirit and concept of the present invention. Unless otherwise specified, all test methods used in the following examples are conventional methods. Unless otherwise specified, all materials, reagents, etc. used in the following examples are commercially available.
[0021] Example 1 This example specifically provides a method for preparing the composition of the present invention, which comprises the following steps: Step 1: Microsphere production Polycaprolactone blend modification: ε-caprolactone, lactide, polyethylene glycol (molecular weight 2000), and toluene were added to a reaction vessel in a mass ratio of 2:1:1:2, and one drop of tin(II) di(2-ethylhexanoate) was added as a catalyst. The pressure was repeatedly reduced at 125°C, oxygen was removed by introducing nitrogen, and the vessel was sealed. The reaction was carried out at this temperature for 48 hours to obtain a product, which was dissolved in chloroform, washed again, purified, and further vacuum dried to obtain a polylactic acid-polycaprolactone-polyethylene glycol copolymer. Tetrahydrofuran and dichloromethane were used as solvents (volume ratio of the two solvents was 1:9), which were mixed with the polylactic acid-polycaprolactone-polyethylene glycol copolymer (PCL ratio was 50 wt%, viscosity was 1.2 dl / g) produced above to prepare an oil phase, in which the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer was 8%. Polyvinyl alcohol (with a viscosity of 25 mPa·s) and Tween 80 were used as solutes (the mass ratio of the two solutes was 10:1), and purified water was added to prepare the aqueous phase, where the mass fraction of the solute was 1%. The volume ratio of the oil phase to the water phase was 1:6.
[0022] Preparation of microspheres by membrane emulsification method: The oil phase was extruded at a pressure of 0.2 kPa, and permeated through a membrane with a pore size of 20 μm, and mixed with the water phase (under ice bath conditions at 4-8 ° C) while stirring (stirring speed is 250 r / min). After the oil phase was completely permeated through the membrane, the mixture was emulsified by continuing to stir at the same speed for 30 minutes, and then the ice bath was removed. Then, the mixture was stirred at 250 r / min at 21 ° C for 4 hours to volatilize the solvent of the oil phase. The prepared microspheres were washed with water 3-5 times. The particle size of the obtained microspheres was in the range of 30-50 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 75.6% of the total mass of the microspheres).
[0023] Step 2: Preparation of the dispersion 240 mg of cross-linked sodium hyaluronate (molecular weight 1500000), 12 mg of mussel adhesive protein, and 100 mg of glycerol were dissolved in phosphate buffer (prepared according to Chinese Pharmacopoeia 20208002, pH 7.3) and the volume was adjusted to 10 ml. The osmotic pressure was adjusted to 300 mOsm / L with sodium chloride to obtain gel dispersion A.
[0024] Step 3: Preparation of the composition A solution with a mass fraction of 15% was prepared by adding water to 2.4 mg of PEG-SG (4 arms, molecular weight 10000), and then freeze-dried to obtain a freeze-dried powder (pre-frozen at -40°C for 3 hours, then dried at a vacuum of 0.2 mbar for 20 hours, 8 hours, 2 hours, and 2 hours at a temperature gradient of -28°C, -18°C, 10°C, and 30°C, respectively, to obtain a freeze-dried powder). This was added to the gel dispersion A obtained in step 2 together with the microspheres after sieving in step 1, and mixed uniformly to obtain a uniform composition. The ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 7.5:2.5.
[0025] Example 2 This example specifically provides a method for preparing the composition of the present invention, which comprises the following steps: Step 1: Microsphere production Polycaprolactone blend modification: ε-caprolactone, lactide, polyethylene glycol (molecular weight 2000), and toluene were added to a reaction vessel in a mass ratio of 4:3:3:10, and one drop of tin(II) di(2-ethylhexanoate) was added as a catalyst. The pressure was repeatedly reduced at 125°C, oxygen was removed by introducing nitrogen, and the vessel was sealed. The reaction was carried out at this temperature for 60 hours to obtain a product, which was dissolved in chloroform, washed again, purified, and further vacuum dried to obtain a polylactic acid-polycaprolactone-polyethylene glycol copolymer. Tetrahydrofuran and dichloromethane were used as solvents (volume ratio of the two solvents was 2:8), which were mixed with the polylactic acid-polycaprolactone-polyethylene glycol copolymer (PCL ratio was 40 wt%, viscosity was 1.5 dl / g) produced above to prepare an oil phase, in which the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer was 15%. Polyvinyl alcohol (with a viscosity of 5 mPa·s) and Tween 80 were used as solutes (the mass ratio of the two solutes was 9:1), and purified water was added to prepare the aqueous phase, where the mass fraction of the solute was 3%. The volume ratio of the oil phase to the water phase was 1:10.
[0026] Preparation of microspheres by membrane emulsification method: The oil phase was extruded at a pressure of 0.4 kPa, permeated through a membrane with a pore size of 10 μm, and mixed with the water phase (under ice bath conditions at 4-8 ° C) while stirring (stirring speed is 200 r / min). After the oil phase was completely permeated through the membrane, the mixture was emulsified by continuing to stir at the same speed for 10 minutes, and then the ice bath was removed. The mixture was then stirred at 200 r / min at 22 ° C for 4 hours to volatilize the solvent in the oil phase. The prepared microspheres were washed with water 3-5 times. The particle size of the obtained microspheres was in the range of 20-60 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 49.6% of the total mass of the microspheres).
[0027] Step 2: Preparation of the dispersion 240 mg of cross-linked sodium hyaluronate (molecular weight 1500000), 12 mg of mussel adhesive protein, and 100 mg of glycerol were dissolved in phosphate buffer (prepared according to Chinese Pharmacopoeia 20208002, pH 7.3) and the volume was adjusted to 10 ml. The osmotic pressure was adjusted to 310 mOsm / L with sodium chloride to obtain gel dispersion A.
[0028] Step 3: Preparation of the composition 2.4 mg of lyophilized powder of PEG-SG (4 arms, molecular weight 10,000) (prepared in the same manner as in Example 1) was added to the gel dispersion A obtained in step 2 together with the sieved microspheres in step 1 and mixed uniformly to obtain a homogeneous composition. The ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 7.5:2.5.
[0029] Example 3 Step 1: Microsphere production Polycaprolactone blend modification: ε-caprolactone, lactide, polyethylene glycol (molecular weight 2000), and toluene were added to a reaction vessel in a mass ratio of 2:1:1:2, and one drop of tin(II) di(2-ethylhexanoate) was added as a catalyst. The pressure was repeatedly reduced at 125°C, oxygen was removed by introducing nitrogen, and the vessel was sealed. The reaction was carried out at this temperature for 48 hours to obtain a product, which was dissolved in chloroform, washed again, purified, and further vacuum dried to obtain a polylactic acid-polycaprolactone-polyethylene glycol copolymer. Pure dichloromethane was used as a solvent and mixed with the polylactic acid-polycaprolactone-polyethylene glycol copolymer (PCL content: 50 wt %, viscosity: 1.2 dl / g) produced above to prepare an oil phase, in which the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer was 2%. Polyvinyl alcohol (with a viscosity of 50 mPa·s) was used as the solute, and pure water was added to prepare the aqueous phase, where the mass fraction of the solute was 0.1%. The volume ratio of the oil phase to the water phase was 1:4.
[0030] Preparation of microspheres by membrane emulsification method: The oil phase is extruded at a pressure of 0.1 kPa, passed through a membrane with a pore size of 20 μm, and mixed with the water phase (under the condition of 4-8 ° C ice bath) while stirring (stirring speed is 500 r / min). After the oil phase is completely permeated through the membrane, it is emulsified by continuing to stir at 500 r / min for 60 minutes, then the ice bath is removed, and the solvent of the oil phase is volatilized by continuing to stir at 500 r / min for 4.5 hours at 18 ° C. The produced microspheres were washed with water 3 to 5 times. The particle size of the obtained microspheres is in the range of 25 to 60 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 61.7% of the total mass of the microspheres).
[0031] Step 2: Preparation of the dispersion 240 mg of cross-linked sodium hyaluronate (molecular weight 1500000), 12 mg of mussel adhesive protein, and 100 mg of glycerol were dissolved in phosphate buffer (prepared according to Chinese Pharmacopoeia 20208002, pH 7.3) and the volume was adjusted to 10 ml. The osmotic pressure was adjusted to 280 mOsm / L with sodium chloride to obtain gel dispersion A.
[0032] Step 3: Preparation of the composition 2.4 mg of lyophilized powder of PEG-SG (4 arms, molecular weight 10,000) (prepared in the same manner as in Example 1) was added to the gel dispersion A obtained in step 2 together with the sieved microspheres in step 1 and mixed uniformly to obtain a homogeneous composition. The ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 7.5:2.5.
[0033] Example 4 This example specifically provides a method for preparing the composition of the present invention, which comprises the following steps: Step 1: Microsphere production Polycaprolactone blend modification: ε-caprolactone, lactide, polyethylene glycol (molecular weight 2000), and toluene were added to a reaction vessel in a mass ratio of 2:1:1:2, and one drop of tin(II) di(2-ethylhexanoate) was added as a catalyst. The pressure was repeatedly reduced at 125°C, oxygen was removed by introducing nitrogen, and the vessel was sealed. The reaction was carried out at this temperature for 48 hours to obtain a product, which was dissolved in chloroform, washed again, purified, and further vacuum dried to obtain a polylactic acid-polycaprolactone-polyethylene glycol copolymer. Tetrahydrofuran and dichloromethane were used as solvents (volume ratio of the two solvents was 1:9), which were mixed with the polylactic acid-polycaprolactone-polyethylene glycol copolymer (PCL ratio was 50 wt%, viscosity was 1.2 dl / g) produced above to prepare an oil phase, in which the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer was 8%. Polyvinyl alcohol (with a viscosity of 25 mPa·s) and Tween 80 were used as solutes (the mass ratio of the two solutes was 10:1), and purified water was added to prepare the aqueous phase, where the mass fraction of the solute was 1%. The volume ratio of the oil phase to the water phase was 1:6.
[0034] Preparation of microspheres by membrane emulsification method: The oil phase is extruded at a pressure of 0.2 kPa, permeated through a membrane with a pore size of 20 μm, and mixed with the water phase (under ice bath conditions at 4 to 8 ° C) while stirring (the stirring speed is 250 r / min). After the oil phase is completely permeated through the membrane, it is emulsified by continuing to stir at 250 r / min for 30 minutes, then the ice bath is removed, and the solvent of the oil phase is volatilized by continuing to stir at 250 r / min for 5 hours at 16 ° C. The produced microspheres were washed with water 3 to 5 times. The particle size of the obtained microspheres is in the range of 30 to 50 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 72.4% of the total mass of the microspheres).
[0035] Step 2: Preparation of the dispersion 300 mg of cross-linked sodium hyaluronate (molecular weight 1,000,000), 12 mg of mussel adhesive protein, and 50 mg of glycerol were dissolved in phosphate buffer (prepared according to Chinese Pharmacopoeia 20208002, pH 7.3) and the volume was adjusted to 10 ml. The osmotic pressure was adjusted to 320 mOsm / L with sodium chloride to obtain gel dispersion A.
[0036] Step 3: Preparation of the composition 2.5 mg of lyophilized powder of PEG-SG (4 arms, molecular weight 5000) (prepared in the same manner as in Example 1) was added to the gel dispersion A obtained in step 2 together with the sieved microspheres in step 1 and mixed uniformly to obtain a homogeneous composition. The ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 6:4.
[0037] Example 5 This example specifically provides a method for preparing the composition of the present invention, which comprises the following steps: Step 1: Microsphere production Polycaprolactone blend modification: ε-caprolactone, lactide, polyethylene glycol (molecular weight 2000), and toluene were added to a reaction vessel in a mass ratio of 2:1:1:2, and one drop of tin(II) di(2-ethylhexanoate) was added as a catalyst. The pressure was repeatedly reduced at 125°C, and oxygen was removed by introducing nitrogen. After sealing, the mixture was reacted at this temperature for 48 hours to obtain a product. The product was dissolved in chloroform, washed again, purified, and further dried in vacuum to obtain a polylactic acid-polycaprolactone-polyethylene glycol copolymer. Tetrahydrofuran and dichloromethane were used as solvents (volume ratio of the two solvents was 1:9), which were mixed with the polylactic acid-polycaprolactone-polyethylene glycol copolymer (PCL ratio was 50 wt%, viscosity was 1.2 dl / g) produced above to prepare an oil phase, in which the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer was 8%. Polyvinyl alcohol (with a viscosity of 25 mPa·s) and Tween 80 were used as solutes (the mass ratio of the two solutes was 10:1), and purified water was added to prepare the aqueous phase, where the mass fraction of the solute was 1%. The volume ratio of the oil phase to the water phase was 1:6.
[0038] Preparation of microspheres by membrane emulsification method: The oil phase was extruded at a pressure of 0.2 kPa, permeated through a membrane with a pore size of 20 μm, and mixed with the water phase (under ice bath conditions at 4-8 ° C) while stirring (the stirring speed was 250 r / min). After the oil phase was completely permeated through the membrane, the mixture was emulsified by continuing to stir at 250 r / min for 30 minutes, and then the ice bath was removed. The mixture was then stirred at 19 ° C for 4 hours at 250 r / min to volatilize the solvent in the oil phase. The prepared microspheres were washed with water 3-5 times. The particle size of the obtained microspheres was in the range of 30-50 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 74.3% of the total mass of the microspheres).
[0039] Step 2: Preparation of the dispersion 150 mg of cross-linked sodium hyaluronate (molecular weight 2,500,000), 10 mg of mussel adhesive protein, and 200 mg of glycerol were dissolved in phosphate buffer (prepared according to Chinese Pharmacopoeia 20208002, pH 7.3) and the volume was adjusted to 10 ml. The osmotic pressure was adjusted to 300 mOsm / L with sodium chloride to obtain gel dispersion A.
[0040] Step 3: Preparation of the composition 1.88 mg of lyophilized powder of PEG-SG (4 arms, molecular weight 40,000) (prepared in the same manner as in Example 1) was added to the gel dispersion A obtained in step 2 together with the sieved microspheres in step 1 and mixed uniformly to obtain a homogeneous composition. The ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 9:1.
[0041] Example 6 This example specifically provides a method for preparing the composition of the present invention, which comprises the following steps: Step 1: Microsphere production Polycaprolactone blend modification: ε-caprolactone, lactide, polyethylene glycol (molecular weight 2000), and toluene were added to a reaction vessel in a mass ratio of 4:1:1:4, and one drop of tin(II) di(2-ethylhexanoate) was added as a catalyst. The pressure was repeatedly reduced at 125°C, and oxygen was removed by introducing nitrogen. After sealing, the mixture was reacted at this temperature for 12 hours to obtain a product. The product was dissolved in chloroform, washed again, purified, and further vacuum dried to obtain a polylactic acid-polycaprolactone-polyethylene glycol copolymer. Tetrahydrofuran and dichloromethane were used as solvents (volume ratio of the two solvents was 1:9), which were mixed with the polylactic acid-polycaprolactone-polyethylene glycol copolymer (PCL ratio was 70 wt%, viscosity was 0.15 dl / g) produced above to prepare an oil phase, in which the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer was 8%. Polyvinyl alcohol (with a viscosity of 25 mPa·s) and Tween 80 were used as solutes (the mass ratio of the two solutes was 10:1), and purified water was added to prepare the aqueous phase, where the mass fraction of the solute was 1%. The volume ratio of the oil phase to the water phase was 1:6.
[0042] Preparation of microspheres by membrane emulsification method: The oil phase was extruded at a pressure of 0.2 kPa, permeated through a membrane with a pore size of 20 μm, and mixed with the water phase (under ice bath conditions at 4-8 ° C) while stirring (stirring speed is 250 r / min). After the oil phase was completely permeated through the membrane, it was emulsified by continuing to stir at 250 r / min for 30 minutes, then the ice bath was removed, and the solvent in the oil phase was volatilized by continuing to stir at 250 r / min at 20 ° C for 4 hours. The produced microspheres were washed with water 3-5 times. The particle size of the obtained microspheres was in the range of 20-60 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 53.5% of the total mass of the microspheres).
[0043] Step 2: Preparation of the dispersion 240 mg of cross-linked sodium hyaluronate (molecular weight 1500000), 12 mg of fibroin protein, and 100 mg of glycerol were dissolved in phosphate buffer (prepared according to Chinese Pharmacopoeia 20208002, pH 7.3) and the volume was adjusted to 10 ml. The osmotic pressure was adjusted to 300 mOsm / L with sodium chloride to obtain gel dispersion A.
[0044] Step 3: Preparation of the composition 2.4 mg of lyophilized powder of PEG-SG (4 arms, molecular weight 40,000) (prepared in the same manner as in Example 1) was added to the gel dispersion A obtained in step 2 together with the sieved microspheres in step 1 and mixed uniformly to obtain a homogeneous composition. The ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 7.5:2.5.
[0045] Example 7 This example provides a method for preparing the composition. The specific preparation method is the same as that in Example 1. The only difference between the two is that the preparation method for the microspheres is changed from the membrane emulsification method to the shear emulsification method. Preparation of microspheres by shear emulsification: The specific mechanical stirring parameters were 1000 r / min, and under the condition of an ice bath at 5°C, the oil phase was added dropwise while stirring the aqueous phase, and emulsified by stirring for 30 minutes, then the ice bath was removed, the rotation speed was reduced at 22°C, and the solvent was evaporated for 5 hours by continuing to stir at a speed of 500 r / min, and the prepared microspheres were washed with water 3-5 times. The particle size of the obtained microspheres was in the range of 10-80 μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 36.6% of the total mass of the microspheres).
[0046] Example 8 This example provides a method for preparing the composition. The specific preparation method is the same as that in Example 1. The only difference between the two is that the preparation method of the microspheres is changed from the membrane emulsification method to the spray drying method. Production of microspheres by spray drying: An oil phase with a mass fraction of polylactic acid-polycaprolactone-polyethylene glycol copolymer of 15% was prepared. The oil phase was charged into a spray drying apparatus, and the parameters were set as follows: inlet temperature 85°C, outlet temperature 25°C, supply rate 25ml / min, and high-pressure air flow rate 600L / h. The particle size of the obtained microspheres was in the range of 5-60μm. The microspheres obtained above were sieved to obtain microspheres with particle sizes of 35 to 45 μm (accounting for 38.2% of the total mass of the microspheres).
[0047] Comparative Example 1 This comparative example provides a method for preparing the composition, the specific preparation method is the same as that of Example 1, and the only difference between the two is that polycaprolactone (molecular weight 8000) is used as the raw material for producing the polymer microspheres instead of polylactic acid-polycaprolactone-polyethylene glycol copolymer. Specifically, the particle size of the obtained microspheres is in the range of 5 to 65 μm. The microspheres obtained above are sieved to obtain microspheres with a particle size of 35 to 45 μm (accounting for 38.7% of the total mass of the microspheres).
[0048] Comparative Example 2 This comparative example provides a method for preparing the composition. The specific preparation method is the same as that in Example 1. The only difference between the two is that the freeze-dried powder of polyethylene glycol-propionaldehyde (4 arms, molecular weight 10,000) is used to prepare the composition instead of the freeze-dried powder of polyethylene glycol succinimidyl glutarate.
[0049] Comparative Example 3 This comparative example provides a method for preparing the composition. The specific preparation method is the same as that of Example 1. The only difference between the two is that the cross-linked sodium hyaluronate in Example 1 is changed to CMC-Na (molecular weight 700,000) as a component of gel dispersion A.
[0050] Comparative Example 4 This comparative example provides a method for preparing the composition. The specific preparation method is the same as that in Example 1, and the only difference between the two is that the ratio of the total mass of PEG-SG and gel dispersion A to the mass of the microspheres was 10:1.
[0051] Comparative Example 5 This comparative example provides a method for preparing the composition, and the specific preparation method is the same as that of Example 1. The only differences between the two are that the amount of cross-linked sodium hyaluronate (molecular weight 1,500,000) used is 100 mg, the mass ratio of cross-linked sodium hyaluronate to mussel adhesive protein is 30:1, the mass of mussel adhesive protein is 3.3 mg, and the mass of polyethylene glycol succinimidyl glutarate is 1 mg.
[0052] Comparative Example 6 This comparative example provides a method for preparing a composition, and the specific preparation method is the same as that of Example 1. The only difference between the two is that the mass fraction of polylactic acid-polycaprolactone-polyethylene glycol copolymer in the oil phase was 1%, and the mass fraction of the emulsifier in the aqueous phase was 4%. The other steps were the same as those of Example 1, and the obtained microspheres had a particle size in the range of 1 to 45 μm. The microspheres obtained above were sieved to obtain microspheres with a particle size of 35 to 45 μm (accounting for 34.8% of the total mass of the microspheres).
[0053] Test Example 1 In this test example, the performance of the compositions prepared in the above examples and comparative examples was measured. The specific methods and results are as follows. Observation of microsphere morphology: After washing and air drying, a small amount of the microspheres was taken and the appearance of the microspheres was observed using a scanning electron microscope with lenses of 200 and 500 magnification.
[0054] Measurement of swelling ratio: After the composition was made into a lump, it was cut into a specified shape, and its mass was precisely measured and designated as M1. It was then transferred to a ground joint Erlenmeyer flask, and a phosphate buffer solution of pH 7.2-7.4 preheated to 37°C was added (the amount of the solution used was at least 10 times the mass of the test sample). After 24 hours, the sample was taken out, the moisture on its surface was absorbed with filter paper, and the mass of the gel was precisely measured and designated as M2. Mass swelling ratio = (M2-M1) / M1 x 100%.
[0055] Decomposition cycle considerations: The samples were sealed and placed in a constant temperature shaking water bath at 37°C, and the samples were taken out every month to observe the degree of decomposition of the microspheres.
[0056] Hydrophilicity Test: The microspheres were separated from the composition and dissolved in dichloromethane, and then allowed to volatilize naturally on a slide glass to form a polymer film. The slide glass with the film was then set in a contact angle meter to measure the contact angle of the polymer film.
[0057] Storage stability considerations: The sample was sealed and filled into a syringe, which was then placed vertically at room temperature in a dark environment, and the state of sedimentation and aggregation of the microspheres in the sample was observed every other day.
[0058] Cytocompatibility testing: Smooth muscle cells (purchased from Suzhou Beina Chuanglian Biotechnology Co., Ltd.) were resuscitated and cultured. When they reached 80% confluence, they were subcultured, and the same weight of the compositions prepared in the Examples and Comparative Examples was inoculated. The inoculated smooth muscle cells were then digested to prepare a cell suspension, and 5 × 10 3 The suspension was added to a cell density of 10 cells / well, and smooth muscle cell medium was added up to 100 μl. The cells were then incubated at 37°C, 5% CO 2 The cells were cultured in a cell culture incubator for 7 days, and 4 duplicate wells were prepared for each group of samples. The cell growth status was observed under a scanning electron microscope, live / dead cells were counted by fluorescent staining, and the cell proliferation status in the measurement material was measured by detecting the absorbance value at a wavelength of 450 nm using the CCK8 method. The relative proliferation rate of cells = live cells / dead cells.
[0059] In vivo animal studies: (1) Forty-eight pure-breed New Zealand white rabbits, aged 4 to 6 months and weighing 210 to 215 g, were used as test animals, which were randomly divided into eight groups, six rabbits per group. Group 1 was tested against the composition of Example 1, group 2 was tested against the composition of Example 4, group 3 was tested against the composition of Example 5, group 4 was tested against the composition of Example 6, group 5 was tested against the composition of Comparative Example 3, group 6 was tested against the composition of Comparative Example 4, group 7 was tested against the composition of Comparative Example 5, and group 8 was tested against the composition of Comparative Example 6. (2) On the day of injection, the rabbit's back was shaved, disinfected with iodine tincture and ethanol in the usual way, and injected into a total of 10 sites (0.5 mL / site) at 2 cm intervals subcutaneously on both sides of the spine, and then the injection sites were labeled with Coomassie Brilliant Blue. To prevent fading due to metabolism, the dye was replenished at the injection sites every 2 weeks. (3) All animals were observed at three times after each injection (1 week, 1 month, and 3 months), and the test animals were sacrificed at the 3-month time point. The subcutaneous tissue containing the injected material was excised, immersed in a 10% volumetric formaldehyde solution, and fixed for 48 hours. The tissue was then dehydrated, cleared, infiltrated with paraffin, embedded, and sectioned in the usual manner, with the section thickness set at 3 μm. The diameters (horizontal radius, vertical radius, and two inclined radii, as well as the thickness at the center, were measured for all skin mounds immediately after injection and at the 1-week point, and the average value was taken as the radius r of the hemisphere) and the volume (volume = 2 / 3πr 3 The volume test was carried out immediately after injection, and the volume of all the examples and comparative examples was 0.48 to 0.5 cm. 3 There was no significant difference. One month after the injection, the animals were not sacrificed, and the local appearance reaction and the inflammatory reaction at the injection site were observed. The test results are shown in Tables 1 and 2.
[0060] [Table 1]
[0061] [Table 2]
[0062] Although the present invention has been described in detail above through the general description and specific embodiments, it is obvious to those skilled in the art that some modifications and improvements can be made based on the present invention. Therefore, all such modifications and improvements made without departing from the spirit of the present invention are within the scope of the present invention.
Claims
1. comprising polymer microspheres, polyethylene glycol succinimidyl glutarate, and a dispersion; The polymer microspheres are polylactic acid-polycaprolactone-polyethylene glycol copolymers; the dispersion comprises cross-linked sodium hyaluronate and a protein; The protein is a mussel adhesive protein or a fibroin protein. A composition comprising:
2. the mass ratio of the protein to the cross-linked sodium hyaluronate is 1:(15-25); and / or the mass ratio of the cross-linked sodium hyaluronate to the polyethylene glycol succinimidyl glutarate is (80-120):
1. The composition of claim 1 .
3. The ratio of the total mass of the polyethylene glycol succinimidyl glutarate and the dispersion liquid to the mass of the polymer microspheres is (6 to 9):(1 to 4). The composition according to claim 2 .
4. the dispersion further comprises a phosphate buffer and glycerol, the osmotic pressure is 250 to 350 mOsm / L, and the concentration of the cross-linked sodium hyaluronate in the dispersion is 15 to 30 mg / ml; and / or the mass fraction of the glycerol in the dispersion is 0.48 to 2%. The composition according to any one of claims 1 to 3.
5. The intrinsic viscosity of the polymer microsphere is 0.15 to 1.5 dl / g, and the proportion of PCL in the polymer is 40 to 70 wt %; and / or the polyethylene glycol succinimidyl glutarate is 4-armed and has a molecular weight of 5,000 to 40,000; And / or, the molecular weight of the cross-linked sodium hyaluronate is 1,000,000 to 2,500,000. The composition according to any one of claims 1 to 4.
6. A method for preparing a composition according to any one of claims 1 to 5, comprising the steps of: The method includes the steps of producing polymer microspheres by shear emulsification, membrane emulsification or spray drying, The step of producing the polymer microspheres comprises a step of obtaining an oil phase by mixing an organic solvent with a polylactic acid-polycaprolactone-polyethylene glycol copolymer; The organic solvent is one or more of dichloromethane, tetrahydrofuran, and chloroform. A method comprising:
7. The organic solvent is dichloromethane or a mixed solvent of tetrahydrofuran and dichloromethane in a volume ratio of (1-2):(8-10).
7. The method of claim 6.
8. When the production is carried out by the membrane emulsification method, the process further comprises the steps of: obtaining an aqueous phase by mixing an emulsifier with water; permeating the oil phase through a membrane at a pressure of 0.1 to 0.4 kPa, mixing it with the aqueous phase while stirring at 4 to 8°C (the stirring speed is 200 to 500 r / min, and the pore size of the membrane is 10 to 20 μm); after the permeation of the oil phase through the membrane is complete, continuing to stir for 10 to 60 minutes to emulsify; and then continuing to stir at 15 to 25°C to volatilize the solvent in the oil phase. In the case of producing by the shear emulsification method, the process comprises the steps of: obtaining an aqueous phase by mixing an emulsifier with water; dropping and mixing the oil phase into the aqueous phase while stirring at 4 to 8°C (the stirring speed is 800 to 1000 r / min, and the stirring time is 20 to 40 minutes); and subsequently continuing to stir at 15 to 25°C at a speed of 400 to 500 r / min for 3 to 5 hours. When the oil phase is spray-dried, the oil phase is spray-dried, and the inlet temperature during the spray-drying process is 60-85° C., the outlet temperature is 25-50° C., the supply rate is 10-25 ml / min, and the high-pressure air flow rate is 400-600 L / hr; The emulsifier is one or more of polyvinyl alcohol, Span, Tween (registered trademark), and carboxymethyl cellulose; And / or, the volume ratio of the oil phase to the aqueous phase is 1:(4 to 10).
8. The method according to claim 6 or 7.
9. The emulsifier is polyvinyl alcohol or a mixed solvent of polyvinyl alcohol and Tween 80 (registered trademark) in a mass ratio of (9 to 10):
1.
9. The method of claim 8.
10. The method according to claim 8, wherein the mass fraction of the polylactic acid-polycaprolactone-polyethylene glycol copolymer in the oil phase is 2 to 15%, and the mass fraction of the emulsifier in the aqueous phase is 0.1 to 3%.
11. Use of a composition according to any one of claims 1 to 5 or prepared by the method according to any one of claims 6 to 10 in an injectable dermal filler product.
Citation Information
Patent Citations
Blood vessel embolus material
JP2004167229A
Compositions and methods using hyaluronic acid and hyaluronic acid inhibitors
JP2008509935A
Pentablock polymer, production method, and drug filling
JP2016520141A
Biodegradable phase-separated thermoplastic multiblock copolymers
JP2022550581A
